Near-Infrared Photodetection Based on a Graphene/Intercalated-Graphene Junction - Farhad Larki; Arash Dehzangi; Alam Abedini; Muhamad Ramdzan Buyong; Hossein Tavakol; Parviz Kameli; Md. Shabiul Islam; Hadi Salamati (IEEE Photonics Journal)
Graphene holds unique properties such as high mobility and optical transparency, along with flexibility, robustness and environmental stability, which makes it shine amongst 2D materials in the future of photonics and optoelectronic devices. In this work, a near infrared photodetector is demonstrated based on pristine graphene/metal intercalated graphene junction formation. The graphene intended for intercalation was grown using chemical vapor deposition (CVD), while pristine graphene was obtained through pulsed laser deposition (PLD). A tapered aluminum microelectrode has been used for the electrical contacts to improve the detection of photogenerated carriers during the illumination. The near infrared detection was demonstrated, responsivity and quantum efficiency were tested at room temperature as well as low temperature and the mechanism of photogeneration was explained.